A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 3 - 8. continued. (iii) Would this arrangement enable continuance of contributory scheme facilities? No. (iv) Do you consider that a proposal of this kind is justified on the grounds that the White Paper proposals do not provide freedom of choice of hospital by the patient but they do recommend that the voluntary hospitals must continue to be self-reliant for a portion of their income? or No. (v) Would you consider that such an arrangement would involve an undesirable form of discrimination? Yes. 9. Do you consider that the Government payment should relate to the patient treated, or to the bed provided? i.e. should a patient who prefers a pay-bed benefit financially by the Government payment to the same extent as a patient in a general ward bed? Payment to relate to the patient treated. 10. Are you in favour of such payments as may be made contractually to the Voluntary Hospitals being made (a) Solely from Central Government funds, as suggested in the attached Memorandum? or (b) In part from Central Government funds and in part from Local Authorities? (i.e. Joint Authorities). Solely from Central Government Funds. 11. Do you consider that capital monies required for extensions, under an a proved Area Plan, should be paid to Voluntary Hospitals from Central Government funds, on the same basis as may be available to Local Authorities from time to time, or from the Local Authorities? From Local Authority. 12. Does your Hospital hold any capital funds or other assets of which it would be deprived, under the terms of the bequest, if the Hospital were to become wholly financed by the State or by the Local Authority, i.e. if it ceased to be a Voluntary Hospital in the generally accepted sense? If so, please state the capital sum involved (unless this would involve considerable search). No. 13. Has your Hospital evidence as to whether your voluntary income, including bequests promised or anticipated, has yet been affected by the publication of the White Paper? No. (contd.) 292/847/2/33